Success Rate of Artificial Insemination in Bali Cattle in Madang Suku III Subdistrict, East Ogan Komering Ulu Regency, South Sumatra: Success Rate of Artificial Insemination in Bali Cattle in Madang Suku III Subdistrict, East Ogan Komering Ulu Regency, South Sumatra - Ibrahim Abdul Aziz; Riko Herdiansah; Miki Suhadi; Ambo Asek (Fakultas Peternakan Universitas Tulang Bawang, 2026)
improving productivity and efficiency in cattle farming systems, including Bali cattle production. This study aimed to determine the success rate of artificial insemination in Bali cattle in Madang Suku III District, East Ogan Komering Ulu Regency, South Sumatra Province. The research was conducted from April to May 2025, involving 30 cattle farmers as respondents and 73 female Bali cattle as research objects. The research method applied was a survey approach, with primary data collected through interviews and field observations, and secondary data obtained from literature studies. The success of artificial insemination was evaluated using Service per Conception (S/C) and Conception Rate (CR) indicators. The results showed that the majority of farmers were in the productive age group of 41–50 years, predominantly male, with senior high school education, and more than 20 years of farming experience. The Service per Conception (S/C) value was 1.42, while the Conception Rate (CR) was 60.27%, which are within the acceptable standard range for reproductive performance in smallholder farming systems. These findings indicate that the implementation of artificial insemination in Bali cattle in Madang Suku III District was relatively effective and efficient. The success of AI was influenced by the accuracy of insemination timing, estrus detection ability, inseminator competence, physiological condition of the animals, and overall herd management. Artificial insemination technology has strong potential to be further developed to enhance reproductive efficiency and productivity of Bali cattle.